THE EXPERIENCE AT THE FACULTY OF MEDICINE OF THE UNIVERSITY OF BUENOS AIRES - Valeria Forlizzi (Asociación Argentina de Anatomía Clínica, 2023)
The presence of women in anatomy training and research in health sciences degrees has historically been limited due to gender barriers. However, in recent decades there has been a growing presence and collaboration of women in the teaching and research of human anatomy, so that their role has become increasingly relevant and important. Historically, the teaching of anatomy was based on the analysis and explanation of the male body with certain characteristics. However, women have made significant contributions to the understanding of anatomy, which has resulted in important advances in research and clinical practice. In Argentina, as in other parts of the world, the role of women in anatomy education and research for health science careers has evolved over time. Although historically there have been fewer women than men in these fields, today the numbers are changing and women now represent a significant proportion of students entering health science careers. Women's collaboration in anatomy learning, education and knowledge has increased in recent decades, although there are still challenges in achieving gender balance in this area.